2001
DOI: 10.1021/ac001447t
|View full text |Cite
|
Sign up to set email alerts
|

On-Line High-Precision Stable Hydrogen Isotopic Analyses on Nanoliter Water Samples

Abstract: We describe a new on-line chromium reduction technique for the measurement of stable hydrogen (deltaD) isotopes in waters using continuous-flow isotope ratio mass spectrometry. The on-line Cr reduction method has low intersample memory effects (< 1%) and excellent precision and accuracy for deltaD (+/-0.5% and was used to analyze waters samples as small as 50 nL. The on-line Cr method has a number of significant advantages over conventional offline Zn and U reduction and on-line carbon-based pyrolysis techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
153
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(158 citation statements)
references
References 25 publications
3
153
0
2
Order By: Relevance
“…Water was filtered through a 0.45-mm-pore membrane filter immediately following sampling. Stable isotope analyses were conducted by Environment Canada, Saskatoon, Canada; d 18 O was measured by standard CO 2 -H 2 O equilibration techniques (Koehler et al 2000), whereas d 2 H was determined by the chromium reduction decomposition method of Morrison et al (2001) Sofer and Gat (1972) Temporal and spatial variation in lake hydrology-Previous chemical analysis of these lakes revealed that seasonal changes in lake-water salinity were synchronous among sites during dry summers, but that temporal coherence declined as a function of summer precipitation (Pham et al 2008). In this paper, we compared these seasonal changes in salinity with those of d 18 O and d 2 H to evaluate how evaporative forcing and precipitation may alter the isotopic composition of lake water.…”
Section: Methodsmentioning
confidence: 99%
“…Water was filtered through a 0.45-mm-pore membrane filter immediately following sampling. Stable isotope analyses were conducted by Environment Canada, Saskatoon, Canada; d 18 O was measured by standard CO 2 -H 2 O equilibration techniques (Koehler et al 2000), whereas d 2 H was determined by the chromium reduction decomposition method of Morrison et al (2001) Sofer and Gat (1972) Temporal and spatial variation in lake hydrology-Previous chemical analysis of these lakes revealed that seasonal changes in lake-water salinity were synchronous among sites during dry summers, but that temporal coherence declined as a function of summer precipitation (Pham et al 2008). In this paper, we compared these seasonal changes in salinity with those of d 18 O and d 2 H to evaluate how evaporative forcing and precipitation may alter the isotopic composition of lake water.…”
Section: Methodsmentioning
confidence: 99%
“…Samples collected in 2012 and 2013 were analyzed by continuous flow isotope ratio mass spectrometry using conventional techniques (Epstein and Mayeda, 1953;Morrison et al, 2001), whereas samples collected in 2014 were analyzed by laser absorption technology using a Los Gatos Research liquid water isotope analyzer. …”
Section: Field Sampling and Analysismentioning
confidence: 99%
“…The stable isotopes of hydrogen were measured using a Finnigan DELTA plus XP mass spectrometer working in continuous flow mode by the chromium reduction technique (Morrison et al, 2001). The oxygen isotope composition was measured with a Finnigan DELTA plus mass spectrometer using the classic CO 2 -H 2 O equilibrium method (Horita et al, 1989 …”
Section: Stable Isotopesmentioning
confidence: 99%